2020
DOI: 10.24251/hicss.2020.813
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Repackaged Android Applications Using Perceptual Hashing

Abstract: The last decade has shown a steady rate of Android device dominance in market share and the emergence of hundreds of thousands of apps available to the public. Because of the ease of reverse engineering Android applications, repackaged malicious apps that clone existing code have become a severe problem in the marketplace. This research proposes a novel repackaged detection system based on perceptual hashes of vetted Android apps and their associated dynamic user interface (UI) behavior. Results show that an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Of the 1,260 samples, AVG was able to detect 689 samples (54.7%), Lookout 1,003 samples (79.6%), Norton 254 samples (20.2%), and TrendMicro was able to identify 966 samples (76.7%). Nguyen et al [17,30] reported similar results in a study of AV accuracy in detecting repackaged apps, where a newly repackaged botnet version of the popular Snapchat application was not detected by 12 different AV products including AVG, CM Security, Avast, Norton, Kaspersky, and others. In addition, the representative zero-day sample was not detected by online research engines such as Sandroid, AndroTotal, VirusTotal, and OPSWAT [17].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Of the 1,260 samples, AVG was able to detect 689 samples (54.7%), Lookout 1,003 samples (79.6%), Norton 254 samples (20.2%), and TrendMicro was able to identify 966 samples (76.7%). Nguyen et al [17,30] reported similar results in a study of AV accuracy in detecting repackaged apps, where a newly repackaged botnet version of the popular Snapchat application was not detected by 12 different AV products including AVG, CM Security, Avast, Norton, Kaspersky, and others. In addition, the representative zero-day sample was not detected by online research engines such as Sandroid, AndroTotal, VirusTotal, and OPSWAT [17].…”
Section: Introductionmentioning
confidence: 72%
“…While academicians are interested in detecting malicious activity [17,[30][31], opportunities abound to improve Android malware detection accuracy in commercial AV. Zhou and Jiang [7] evaluated Android malware detection using the following antivirus programs: AVG Antivirus Free v2.9 (AVG), Lookout Security & Antivirus v6.9 (or Lookout), Norton Mobile Security Lite v2.5.0.379 (Norton), and TrendMicro Mobile Security Personal Edition v2.0.0.1294 (TrendMicro).…”
Section: Introductionmentioning
confidence: 99%
“…In the static analysis, the static features are extracted by a specific reverse engineering technique, which does not require running the APK files. The significance of the reverse engineering technique in the static analysis is considered the initial step in preparing a set of features needed for the classification of malware tasks [52].…”
Section: Static Analysismentioning
confidence: 99%
“…Just as example, in modern mobile devices the users can easily download applications from the official market but also from non official ones. These last can be untrustworthy and represent a serious threat for the users' data, in fact users usually consider third-party markets to find free versions of applications that are usually paid ones on the official market [1].…”
Section: Introductionmentioning
confidence: 99%